The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1139/x05-199
|View full text |Cite
|
Sign up to set email alerts
|

Particulate emissions from fires in central Siberian Scots pine forests

Abstract: Siberian boreal forest fires burn large areas annually, resulting in smoke that releases large amounts of particulate emission into the atmosphere. We sampled aerosol emissions from experimental fires on three Scots pine (Pinus sylvestris L.) forest sites of central Siberia. Emissions from ground-based aerosol samples were 0.1-0.7 t/ha. This value represented 1%-7% of the total biomass (10-30 t/ha) consumed during the experimental fires. We were able to classify the chemical composition of 77%-90% of the mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…In the latter study of particles up to 2.5 µm diameter, the BC/TC ratio was found to be 0.085 for the flaming stage and 0.0087 for the smouldering stage, but EFs were not determined. However, more information is recently available from experimental fires in three Scots pine sites of central Siberia (Samsonov et al, 2005). Aerosol emissions corresponded to 1%-7% of the mass of fire-consumed biomass, with EC constituting 7-15% of total aerosol mass.…”
Section: Atmospheric Pyc Emissions From Forest Firesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter study of particles up to 2.5 µm diameter, the BC/TC ratio was found to be 0.085 for the flaming stage and 0.0087 for the smouldering stage, but EFs were not determined. However, more information is recently available from experimental fires in three Scots pine sites of central Siberia (Samsonov et al, 2005). Aerosol emissions corresponded to 1%-7% of the mass of fire-consumed biomass, with EC constituting 7-15% of total aerosol mass.…”
Section: Atmospheric Pyc Emissions From Forest Firesmentioning
confidence: 99%
“…Techniques for visual assessment of char are well-established, but there appear to be no studies with a complete accounting of char in any boreal forest site, and we found no quantitative information on BC storage in boreal peatlands. Integrated projects and interdisciplinary approaches are required, so that, for example, measurements of PyC production could be integrated into experimental fire studies such as the ICFME and FIRE BEAR (Samsonov et al, 2005), and the painstaking efforts to assess char abundance in peat cores could also be used to develop estimates of area-based char stocks. Increased application of 14 C dating is also necessary to assess the turnover time of different fractions of PyC.…”
Section: Towards Understanding and Quantifying The Pyc Cycle In Boreamentioning
confidence: 99%
“…Forest fires play an important role in global atmospheric chemistry. Aerosol emissions from ground-based air samples at three Pinus sylvestris (L.) forest sites in central Siberia that were burned in an experiment ranged from 0.1 to 0.7 t ha Ϫ1 or 1%-7% of the total biomass (10-30 t ha Ϫ1 ) consumed during the experimental fires (Samsonov et al 2005). Anomalies in atmospheric trace gas concentrations from the Commonwealth Scientific and Industrial Research Organisation's (CSIRO) global sampling network in 1994/95 and 1997/98 are consistent with gas emission pulses from extreme fires in the Tropics and the boreal biome (Langenfelds et al 2002).…”
Section: B Backgroundmentioning
confidence: 99%
“…The area of the burn was 26 thousand ha. Average concen trations of the metals in the reference area were as fol lows: Cd, 0.161; Pb, 10 (2) do not imply that all the amounts were transferred far beyond the burn. I showed above that surface fires merely redistributed metals within a burned site or lower forest layers.…”
Section: Resultsmentioning
confidence: 99%
“…Forest understory (grasses and shrubs) added about 5 t/ha on average. The forest floor load reaches 30 t/ha or more for some parts of Central Siberia [10].…”
Section: Objects and Methodsmentioning
confidence: 99%